Ektraksi Ciri Citra Termogram Payudara Berbasis Dimensi Fraktal - Oky Dwi Nurhayati; Thomas Sri Widodo; Adhi Susanto; Maesadji Tjokronagoro (Forum Teknik, 2010)
AbstractThe primary purpose of infrared thermography is the locating of thermal differences and anomalies.  Infrared thermography can  detect  numerous  conditions  in  which  an  anomaly is characterized by an increase or decrease in surface temperature. In this research, we specifically applied calculation of fractal dimension method to a total of20 thermograms of normal breasts as well as of those in advanced breast cancer. In addition standard  image  pre-processing  were  also  used  to  enhance  the  detection capabilitity.  Severalmethods in image processing which are pre-processing with canny edge detection, thresholding, calculation of fractal dimension use box-counting and Hausdorff dimension.The results of this research are shown that Hausdorff dimension in the normal thermogramshave range value 0,4 – 0,95 smaller than the advanced thermograms which have value more than  1,26.Finally  this  results  show  that  the  difference  of  fractal dimension  can  be  used  todistinguish between normal and advanced thermograms.Keywords: canny edge detection, thresholding, fractal dimension, box-counting, Hausdorff